Demystifying Cyber Threat Intelligence: Literature Insights and a Practical Framework (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Cyber Threat Intelligence (CTI) has become increasingly important as organizations face persistent and sophisticated cyberattacks. Modern digital environments—driven by cloud adoption, hyperconnectivity, and automation—require security strategies that anticipate adversarial behavior rather than respond only after incidents occur. This paper presents a concise review of CTI research and industry practices, focusing on intelligence types, analytical models, and operational applications. A streamlined conceptual framework is proposed to help undergraduate- level readers understand how CTI can be integrated into security operations. The framework emphasizes continuous intelligence requirements, structured analysis, and feedback-driven improvement. The review also highlights current limitations in CTI adoption, including data volume challenges, limited analyst expertise, and organizational barriers to information sharing.